(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Mutual Funds have been promoted as a medium for retail investors to get into equity investments and increase their stock market participation. With the ease of investing in small amounts and regular intervals, along with the advantages of diversification of risk and professional management of funds, mutual funds present an attractive avenue of investment. Still the data from Association of Mutual Funds in India (AMFI) does not seem to be reflecting this in terms of growth in mutual fund investments. There is a need to analyse the factors influencing an individual investor’s intentions to invest in mutual funds so as to understand the reasons behind slow growth of mutual fund investments in India and to devise ways to increase the same. This paper analyses the attitudinal, social and behavioural control factors influencing the investor intentions of mutual funds investments using constructs from an extended model of Theory of Planned Behaviour.